Effect of cosmetic matrices on the release and odour profiles of the supercritical CO2 extract of Origanum majorana L. - P. Costa (2016)
ObjectiveIn this study, the effect of different cosmetic matrices on the release profile and odour intensity of the fragrance O. majorana was investigated for the first time. MethodsThe fragrance compounds of O. majorana were extracted by supercritical fluid extraction using carbon dioxide (SFE-CO2) at 40 degrees C and two operating pressures (8.5 and 10 MPa), and their chemical profiles were assessed by gas chromatography with flame ionization detector coupled with mass spectrometry (GC-FID/MS). Lastly, the fragrance compounds were incorporated into three cosmetic matrices (glycerine, dipropylene glycol and skin lotion) to assess their release and odour profiles over time using dynamic headspace (DHS)/GC-FID/MS and Odour Value concept, respectively. ResultsThe SFE-CO2 enabled recovering extracts with the pleasant scent of the living plant, and the increment of pressure induced an increase on the extraction yield. GC-FID/MS analyses revealed that oxygen-containing monoterpenes was the principal group of components identified in both SFE-CO2 extracts. The fragrance compounds were more retained in dipropylene glycol, and the major deviations from the original odour intensity (control) were observed in the presence of dipropylene glycol and skin lotion. ConclusionThe hydrophilic character of the cosmetic matrices strongly influenced the release of the fragrance compounds, thus affecting the odour profile of the studied mixtures. Resume ObjectifDans cette etude, l'effet de differentes matrices cosmetiques sur le profil de liberation et de l'intensite de l'odeur du parfum O. majorana a ete etudie pour la premiere fois. MethodesLes composes parfumes de O. majorana ont ete extraits par extraction de fluide supercritique utilisant le dioxyde de carbone (SFE-CO2) a 40 degrees C et a deux pressions de fonctionnement (8.5 et 10 MPa), et leurs profils chimiques ont ete evalues par chromatographie en phase gazeuse avec detecteur a ionisation de flamme couplee a la spectrometrie de masse (GC-FID/MS). Enfin, les composes de parfum ont ete incorpores dans trois matrices cosmetiques (glycerine, le dipropyleneglycol et lotion pour la peau) afin d'evaluer leurs profils de liberation et d'odeur dans le temps en utilisant le headspace dynamique (DHS)/GC-FID/MS et Odour Value concept, respectivement. ResultatsLe SFE-CO2 a permis la recuperation d'extraits avec l'agreable parfum de la plante vivante, et l'augmentation de la pression induit une augmentation du rendement d'extraction. L'analyse GC-FID/MS a revele que les monoterpenes contenant de l'oxygene etaient le principal groupe de composants identifies dans les deux extraits SFE-CO2. Les composes de parfum sont plus conserves dans le dipropylene glycol; les ecarts majeurs par rapport a l'intensite de l'odeur d'origine (temoin) ont ete observes en presence de dipropylene glycol et dans la lotion pour la peau. ConclusionLe caractere hydrophile des matrices cosmetiques influence fortement la liberation des composes parfumes affectant ainsi le profil de l'odeur des melanges etudies.